The Influence of Communication and Teamwork on Employee Performance with Work Stress as Moderating Variable - Diansyah Diansyah; Dwi Pratiwi (Budapest International Research and Critics University, 2022)
A company will not be able to develop and achieve company goals without the support of human resources. A company if it has good human resources will produce good performance for the company. This study aims to determine the effect of communication and teamwork on employee performance with work stress as a moderating variable. The research method used in this research is quantitative with Partial Least Square (PLS-SEM) technique and assisted by SmartPLS 3.0 software. The researcher chose the census technique in the sampling technique, namely employees in a Jakarta company as the sample in this study to examine the moderating effect and the direct influence of the related variables. The results of this study indicate that there is an effect of communication on employee performance, teamwork affects employee performance, and work stress affects employee performance, work stress is able to moderate communication on performance and work stress is able to moderate teamwork on employee performance. The method of determining the number of respondents' eligibility uses the Hair method which states that the respondent may be 5 to 10 times the number of research variable indicators.